The planning and design of Kampong Pakuncen in Yogyakarta based on the green concept - Setyowati, Erni; Pribadi, Septana Bagus; Aidon Uda, Subrata Aditama K.; Debby, Tiara Rizkyvea; Harsritanto, Bangun I. R. (Journal of Architecture and Urbanism, 2019)
This study aims to determine the green concept of a slum “kampong” with the green concept and carbon footprint approach based on daily activities, building materials and fuel consumption as well as to deliver the concept of renewable energy. The carbon footprint is the measure of total amount of carbon dioxide gas emissions directly or indirectly caused by daily main activities and accumulation of products used daily. It is the case study of Kampong Gampingan-Pakuncen, Yogyakarta. This kampong is known as a densely populated kampong located in the city centre not far from Malioboro, the centre of commercial and business districts in Yogyakarta City. The employed methods were the quantitative-comparative method between carbon footprint of existing and planning condition and the quantitative approach of renewable energy. The results showed that the carbon dioxide concentration of Kampong Pakuncen in the existing condition is 1,712.767 tonnes CO2/month while the total amount of carbon dioxide concentration of the design is 1,293.785 tonnes CO2/month, hence 24.462% carbon dioxide concentration reduction. To save energy consumption in daily activities, it is proposed that water wheel as micro-hydro power should be used for electricity.